CMPK1 and RBP3 are associated with corneal curvature in Asian populations. (24th June 2014) - Chen, Peng; Miyake, Masahiro; Fan, Qiao; Liao, Jiemin; Yamashiro, Kenji; Ikram, Mohammad K.; Chew, Merywn; Vithana, Eranga N.; Khor, Chiea-Chuen; Aung, Tin; Tai, E-Shyong; Wong, Tien-Yin; et al.
Abstract : Corneal curvature (CC) measures the steepness of the cornea and is an important parameter for clinically diseases such as astigmatism and myopia. Despite the high heritability of CC, only two associated genes have been discovered to date. We performed a three-stage genome-wide association study meta-analysis in 12 660 Asian individuals. Our Stage 1 was done in multiethnic cohorts comprising 7440 individuals, followed by a Stage 2 replication in 2473 Chinese and Stage 3 in 2747 Japanese. The SNP array genotype data were imputed up to the 1000 Genomes Project Phase 1 cosmopolitan panel. The SNP association with the radii of CC was investigated in the linear regression model with the adjustment of age, gender and principal components. In addition to the known genes, MTOR (also known as FRAP1 ) and PDGFRA, we discovered two novel genes associated with CC: CMPK1 (rs17103186, P = 3.3 × 10 −12 ) and RBP3 (rs11204213 [Val884Met], P = 1.1 × 10 −13 ). The missense RBP3 SNP, rs11204213, was also associated with axial length (AL) ( P = 4.2 × 10 −6 ) and had larger effects on both CC and AL compared with other SNPs. The index SNPs at the four indicated loci explained 1.9% of CC variance across the Stages 1 and 2 cohorts, while 33.8% of CC variance was explained by the genome-wide imputation data. We identified two novel genes influencing CC, which are related to either corneal shape or eye size. This study provides additional insights into genetic architecture of corneal shape.